Radiographic Changes After Medial Patellofemoral Ligament Reconstruction in Skeletally Immature Patients Compared With an Age- and Sex-Matched Cohort. Issue 3 (March 2023) - Kirby, Julia C.; Brenner, Madison E.; Jones, Hunter; Wilson, Philip L.; Ellis, Henry B.
Background: Despite recent evidence that medial patellofemoral ligament reconstruction (MPFLR) in the skeletally immature patient is both safe and effective, there are limited data evaluating postoperative coronal- and sagittal-plane growth and radiographic patellofemoral parameters in this population. Purpose: The primary purpose was to assess radiographic measures of coronal-plane alignment, longitudinal growth, patellar congruence, and trochlear dysplasia after MPFLR in a skeletally immature population. A secondary purpose was to assess this population compared with a matched cohort with a focus on trochlear dysplasia prevalence and the effect of MPFLR on patellar height. Study Design: Cohort study; Level of evidence, 3. Methods: A total of 28 children with a minimum 1-year follow-up who underwent isolated MPFLR were identified. All patients were skeletally immature, defined as fully open physes on both sides of the knee joint, at the time of surgery. The development of a limb length discrepancy or angular growth abnormalities were assessed on standing hip-to-ankle radiographs, patellar tilt and congruence were measured on the Merchant view of the knee, and the grade of trochlear dysplasia and patellar height were assessed on lateral knee radiographs. A sex- and age-matched group of patients who underwent anterior cruciate ligament reconstruction was formed as a control for patellar height and trochlear dysplasia measurements. Results: The mean patient age was 11.71 ± 2.02 years at the time of surgery with a mean follow-up of 23.54 ± 12.49 months. All but 1 patient in the MPFLR group had preoperative features consistent with trochlear dysplasia. There was no significant difference in limb length or coronal-plane alignment at final follow-up ( P = .725 and P > .999, respectively). Both the MPFLR and the anterior cruciate ligament reconstruction groups had a statistically significant decrease in the Caton-Deschamps index between the preoperative and postoperative time points (mean, 0.18 ± 0.20 and 0.11 ± 0.14, respectively; P = .161). Conclusion: MPFLR may be safely performed utilizing an epiphyseal femoral socket in a skeletally immature cohort without affecting normal longitudinal growth or coronal limb alignment. The previously reported effect of MPFLR in reducing patellar height may be related to physiological growth based on similar changes noted in a comparison cohort that did not undergo the procedure.